(untitled) (Materiali di Estetica. Terza serie, 2023)
From the unconscious of speech to the structure of Id (Es), silent in its colours and forms, the language of colours in psychoanalysis is configured in dreams, children’s drawings and artists’ works as a universal residue of our belonging to nature and at the same time participates, with its grammar, morphology and syntax, in the process of constructing the subject that makes each person unique in his or her own history. As Virginia Finzi Ghisi writes, if we deal with painting as psychoanalysts, it is because “every form of art reflects the structure of the psychic apparatus”.